2022
DOI: 10.1007/s00441-022-03686-x
|View full text |Cite
|
Sign up to set email alerts
|

Lung organoids: current strategies for generation and transplantation

Abstract: Lung diseases occupy a leading position in human morbidity and are the third leading cause of death. Often the chronic forms of these diseases do not respond to therapy, so that lung transplantation is the only treatment option. The development of cellular and biotechnologies offers a new solution-the use of lung organoids for transplantation in such patients. Here, we review types of lung organoids, methods of their production and characterization, and experimental works on transplantation in vivo. These resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Although, to date, only a few studies have explored this possibility, lung organoids represent a potential tool for tissue regenerative approaches [383]. Since it has been discovered that new lung growth can occur in adults [384], the scientific community is focusing on studying lung repair and regeneration as an emerging and promising strategy for the treatment of patients with both acute and chronic lung diseases, which can cause the loss of functional lung tissue, such as that occurring in chronic obstructive pulmonary disease [385], pulmonary fibrosis [386], CF [387], and pulmonary arterial hypertension [388,389].…”
Section: Lungmentioning
confidence: 99%
“…Although, to date, only a few studies have explored this possibility, lung organoids represent a potential tool for tissue regenerative approaches [383]. Since it has been discovered that new lung growth can occur in adults [384], the scientific community is focusing on studying lung repair and regeneration as an emerging and promising strategy for the treatment of patients with both acute and chronic lung diseases, which can cause the loss of functional lung tissue, such as that occurring in chronic obstructive pulmonary disease [385], pulmonary fibrosis [386], CF [387], and pulmonary arterial hypertension [388,389].…”
Section: Lungmentioning
confidence: 99%
“…The utility of organoids to studying disease progression and treatment is endless and have been increasingly employed in either basic or translational research. Despite the use of organoids in studying cancer biology, the novel applications of organoids are the utilization of lung organoids for lung disease that may be transplanted in these individuals instead of undergoing a lung transplant and the generation of vascularized brain organoids that can be utilized to study neurovascular interaction ( 126 , 127 ). Additionally, the generation of skin organoids that have similar complexity of the skin (including the development of hair follicles) and eye organoids that could potentially be used to replace neurons lost in humans due to degenerative eye diseases, therefore providing a potential therapeutic option ( 128 , 129 ).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Several recent studies have reported protocols for generating airway and alveolar organoids using iPSCs, which involve repro- gramming fibroblasts [20,25,26]. Many alveolar organoid protocols also require a cell sorting step, because iPSC differentiation is not efficient enough to progress to the next cell stage (Table 2) [20,21,26,27].…”
Section: Protocol For Generating Alveolar Organoids From At2 and Ucb ...mentioning
confidence: 99%
“…Several recent studies have reported protocols for generating airway and alveolar organoids using iPSCs, which involve repro- gramming fibroblasts [20,25,26]. Many alveolar organoid protocols also require a cell sorting step, because iPSC differentiation is not efficient enough to progress to the next cell stage (Table 2) [20,21,26,27]. Therefore, in this study, we sought to establish iPSC-derived alveolar organoids without the cell sorting step in which full compartment cells are present in a culture using AT2 and UCB iPSCs.…”
Section: Protocol For Generating Alveolar Organoids From At2 and Ucb ...mentioning
confidence: 99%